Manajemen Program Hafalan Al-Qur'an di Pesantren Darul Qur'an Medan: Pendekatan Kualitatif dalam Perancangan, Implementasi, dan Evaluasi - Dona Santika; Rahimah Rahimah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to describe the management of the Quran memorization program at Darul Qur'an Islamic Boarding School in Medan. Utilizing qualitative methods, data were collected through interviews, observations, and documentation. The collected data were then analyzed using the Miles and Huberman model to explore how the boarding school designs and implements its Quran memorization program. The findings indicate that Darul Qur'an Islamic Boarding School has a well-structured Quran memorization program. The principal plays a crucial role in designing the program and providing guidance to teachers. Furthermore, the teachers at the school are creative in employing various teaching methods to maintain student engagement and prevent boredom. Additionally, the boarding school has a clear assessment system to track and measure student progress.